2013
DOI: 10.1007/s13404-013-0091-z
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Gram-positive bacteria are highly sensitive to triphenylphosphanegold(O-alkylthiocarbamates), Ph3PAu[SC(OR)=N(p-tolyl)] (R = Me, Et and iPr)

Abstract: The phosphanegold(I) thiocarbamides, Ph 3 PAu{SC(OR)=NC 6 H 4 Me-4} for R = Me (1), Et (2) and iPr (3), have been shown to have essentially linear gold atom coordination geometries defined by phosphane-P and thiolate-S atoms, and exhibit minimum inhibitory concentration (MIC) values in the range of 1-37 μg/ml against four Gram-positive bacteria, namely Bacillus cereus, Enterococcus faecalis, Enterococcus faecium and Staphylococcus aureus; compounds 1-3 are less potent against a broad panel of 16 Gram-negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 49 publications
(57 reference statements)
1
33
0
Order By: Relevance
“…While 1 and 2, with hydroxyethyl functionalized dithiocarbamate ligands and 4 are new, 3 is a known compound [35] and the crystal structure of 3 is available [47]. A number of studies are now available suggesting that dithiocarbamate ligands with hydroxyethyl groups possess biological activity [43,44,48,49] and therefore it was thought of interest to extend the studies to 1 and 2, given the anti-bacterial activity of R3PAu[S2CN(iPr)CH2CH2OH] for R = Et, Cy and Ph [42]. Compounds 3 and 4 were included in the present study as they contain Et3P, as in Auranofin®, and have conventional dithiocarbamate ligands which have demonstrated biological activity when complexed to metals [36].…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…While 1 and 2, with hydroxyethyl functionalized dithiocarbamate ligands and 4 are new, 3 is a known compound [35] and the crystal structure of 3 is available [47]. A number of studies are now available suggesting that dithiocarbamate ligands with hydroxyethyl groups possess biological activity [43,44,48,49] and therefore it was thought of interest to extend the studies to 1 and 2, given the anti-bacterial activity of R3PAu[S2CN(iPr)CH2CH2OH] for R = Et, Cy and Ph [42]. Compounds 3 and 4 were included in the present study as they contain Et3P, as in Auranofin®, and have conventional dithiocarbamate ligands which have demonstrated biological activity when complexed to metals [36].…”
Section: Chemistrymentioning
confidence: 99%
“…Time-kill studies indicated the R = Cy and Ph compounds were bactericidal whereas the R = Et compound was both bactericidal and bacteriostatic depending on the specific bacterial strain, observations suggesting different mechanisms of action are applicable depending on both the nature of the phosphane ligand and bacteria. Given that earlier studies showed the Et3P ligand in gold compounds [43] and -S2CN(CH2CH2OH)2 ligands in copper and silver compounds [44] furnish active species, the foregoing studies were extended to the four compounds shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…aureus (MRSA), and to be bactericidal [50]. The foregoing suggests this class of compound is well worthy of further, systematic investigation for biological potential and may complement platinum drugs for the treatment of cancer [51].…”
Section: Related Complexesmentioning
confidence: 99%
“…In the context of the former, anions that are derived from thiocarbamates complex phosphanegold(I) species to form molecules of the general formula R″3PAu[SC(OR)=NR′] (R, R′, R″ = alkyl, aryl), compounds that exhibit anti-cancer potential [1] and bactericidal properties [2]. Crystals of these species are often forthcoming enabling the evaluation of systematic variations of the R, R′, and R″ substituents upon the molecular packing and solid-state luminescence [3,4].…”
Section: Introductionmentioning
confidence: 99%